Clinical value and molecular role of PRDXs family in prostate cancer - Yao, Yong; Zheng, Quan; Qian, Chen; Gu, Peng; Zhang, Minhao; Zhang, Zhou (Frontiers in Oncology, 2025)
ObjectivesThe purpose of this study is to explore the clinical value and molecular role of the peroxiredoxins (PRDXs) family in prostate cancer (PCa).MethodsWe first analyzed the differentially expressed genes (DEGs) in Prostatic Adenocarcinoma (PRAD) using the Cancer Genome Atlas (TCGA) database, and then demonstrated the expression of six members of the PRDXs family in PRAD. Subsequently, we evaluated the expression of the PRDXs family using PCa cells and tissues. we also analyzed the diagnosis and overall survival (OS) of the PRDXs family in PCa. We used online tools to analyze the expression of PRDX4 in pan-cancer, the proteins interacting with it, as well as the amino acid regions and sites to pathogenicity. We used CCK8 and transwell assay to detect the proliferation and invasion of PCa cells after silencing PRDX4. Finally, we predicted traditional Chinese medicine drugs targeting PCa with PRDX4.ResultsWe found that PRDX2 and PRDX4 were highly expressed in PRAD through the TCGA database. Compared with prostate epithelial cells, PRDX2, PRDX3, PRDX4, and PRDX6 were expressed higher in PCa cells. In PCa tissues, the PRDXs family is widely expressed positively (P<0.05). The PRDXs family has relatively low diagnostic value in PCa, except for PRDX4. Based on the above results, we selected PRDX4 for molecular role detection. We found that the expression of PRDX4 in PCa was higher than that in more than half of the cancer types in pan-cancer. We found that there are eight proteins interacting with PRDX4. The pathogenic amino acid regions and sites of PRDX4 protein mutation that are prone to disease were mainly concentrated in the area after the 50th amino acid. We found that silencing PRDX4 slowed down the proliferation and invasion of PCa cells. Finally, we found that there are 14 traditional Chinese medicines targeting PCa with PRDX4, among which 5 have statistical differences, and Shi Liu Zi may be the best targeted traditional Chinese medicine drug.ConclusionThis study found that PRDX4 is highly expressed in PCa, which may promote the phenotypic progression of PCa cells and has high clinical value.